Recent advances in the prevention of secondary ischemic stroke: A narrative review - Yue Qiao; Aminah I. Fayyaz; Yuchuan Ding; Xunming Ji; Wenbo Zhao (Brain Circulation)
Stroke remains a significant contributor to global morbidity and mortality, with acute ischemic stroke comprising the majority of cases. Secondary stroke, the recurrent stroke, is often more severe and linked to worse functional outcomes and increased mortality. The secondary prevention of ischemic stroke is crucial for reducing the risk of recurrent events. Significant advancements have been made in secondary prevention strategies in recent years. These include the refinement of antithrombotic regimens, the use of direct oral anticoagulants in managing atrial fibrillation, and the implementation of more aggressive targets for blood pressure, lipid management, and glucose management. Furthermore, emerging therapeutic approaches, such as remote ischemic conditioning and anti-inflammatory agents such as colchicine, have shown promise in reducing stroke recurrence through nontraditional mechanisms. This review summarizes the latest advancements in the secondary prevention of ischemic stroke over the past 5 years, highlighting the key clinical trials and novel interventions. The optimization of traditional risk factor management and the emergence of novel therapeutic methods have provided more options for clinical practice. Future research should focus on identifying the optimal treatment strategies for specific patient subgroups and the clinical translation and application of new therapeutic methods.